Pengaruh Strategi REACT Terhadap Kemampuan Berpikir Kritis Siswa SMA Negeri 4 Merauke - Neneng Amabarwati; Minuk Riyana; Rian Ade Pratama (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This study aims to determine the effect of the implementation of the REACT strategy on critical thinking skills of SMA Negeri 4 Merauke students. This research was an experimental research design with pretest-posttest control group design, where the research was conducted, namely in SMA Negeri 4 Merauke. Hypothesis testing used homogeneity test. The implementation of the REACT strategy is seen through the acquisition of an average posttest score of 75.58 which was more than the average pretest score of 42.65 in the experimental class, with an increase in the moderate category of 0.5738 and based on a paired T-test sample with a sig value. (2-tailed) 0,000 <0.05 which means that there is a difference between the pretest and posttest, in other words the influence of the application of the use of REACT strategies to the critical thinking skills of SMA Negeri 4 Merauke students. Students' thinking skills are better in which students can solve critical thinking questions given in accordance with predetermined scoring indicators, students write what is known from the problems, students make mathematical models, students use strategies in solving problems and are able to make conclusions from solving the given problem. With the test results obtained by students almost weak on the average criteria of the analysis indicators.